Boosting the organizational performance: Ethical climate as a moderator for optimizing risk management practices in the Saudi Public sector - Ahmed Hassan Abdou; Ridhima Sharma; Azzam Ibrahem Ali Albakhit (Global Business & Finance Review (GBFR), 2024)
Purpose: Drawing upon contingency theory, this study aims to investigate the relationship between risk management practices (RMPs), ethical climate (EC), and organizational performance (OP) in public organizations within the Kingdom of Saudi Arabia (KSA). Specifically, the study explores the moderating effect of EC in shaping the relationship between RMPs and OP. Design/methodology/approach: Survey data were collected from a convenience sampling of 392 senior government directors within public organizations in the KSA through an online questionnaire. The relationships between study constructs were analyzed using PLS-SEM with the bootstrapping technique. Findings: The study's findings reveal a significant positive impact of both RMPs and EC on organizational performance. Notably, the research demonstrates that ethical climate significantly moderates the positive relationship between RMPs and OP, highlighting the critical importance of ethical conduct in maximizing the effectiveness of risk mitigation strategies. Research limitations/implications: The study's focus on the Saudi public sector and its use of a convenience sampling technique, primarily comprising senior government directors, are significant limitations when interpreting this study's findings. Expanding research to incorporate diverse organizational settings could significantly enhance this work's generalizability and practical implications. Additionally, focusing solely on EC as a moderator in the RMP-OP relationship overlooks other potentially relevant factors. Future research could delve deeper into the mechanisms through which ethical climate strengthens the impact of RMPs on performance, providing valuable guidance for organizational interventions. Originality/value: This study's originality lies in its first-time examination of ethical climate as a moderator in the relationship between RMPs and organizational performance within Saudi public organizations. Further, study findings expanded the scope of contingency factors demonstrating that a strong ethical climate significantly amplifies the positive impact of RMPs on performance, providing compelling evidence for considering ethical climate as a crucial contingency factor for public sector success.
Keywords: 650; Risk management; Contingency theory; Ethical climate; Public sector; KSA